Sources of psychological and emotional discomfort of students and methodological ways to overcome it - Elena V. Maksimyuk (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The paper analyzes the results of a survey of first-year students of the Siberian State Automobile and Highway University, conducted to identify the problem areas and factors provoking psycho-emotional discomfort among students at the initial stage of education. The prospect of the study is the further development and implementation of effective methods for leveling factors that are sources of psycho-emotional discomfort during the educational process, and creating a comfortable educational environment that provides cognitive and emotional-reflexive inclusion of students in the educational process. The study was carried out in several stages. The results of the first survey made it possible to assess the degree of psycho-emotional comfort of students in 26 different disciplines. At the second stage, the presence of psychological comfort among students in the classroom was analyzed, depending on the nature of the discipline. The third stage of the study was aimed at identifying sources of discomfort. The identified sources were divided into external, associated with the personality of the teacher, and internal, associated with the student himself. Then a further survey was conducted to reveal factors that cause psycho-emotional discomfort. As external factors, the respondents indicated the language personality of the teacher, the manner of presenting the material and the nature of the requirements. Internal factors are the level of respondents own knowledge, self-doubt and uncertainty about the prospects. At the last stage of the study, the respondents had to suggest ways to overcome discomfort in the classroom. An analysis of the answers showed that the majority of respondents are ready to independently solve the problems of psycho-emotional discomfort by improving knowledge, more thorough preparation for classes, raising self-confidence, as well as by timely solving emerging issues and constructive dialogue with the teacher. In the final part, based on the identified sources and factors, methodological recommendations are formulated on how to eliminate the psycho-emotional discomfort of students in the classroom.